Ischemic stroke following reversal of dabigatran with idarucizumab in spontaneous subdural hematoma in cerebral venous thrombosis - Santhosh, Thanisha; Krishnan, Pramod; Anusha, Donti R.; Acharya, Ullas V.; Kalashetty, Mallikarjun (International Journal of Research in Medical Sciences, 2024)
Spontaneous subdural hematomas (SDH) are an unusual but potentially devastating complication of oral anticoagulation. Emergency management of subdural hematomas following oral anticoagulant therapy consists of reversal of anticoagulation coupled with surgical evacuation, if indicated. However, the question of reintroducing anticoagulants is a conundrum faced by clinicians. Clinical equipoise remains divergent among neurologists and literature guiding them is sparse. We report a case of spontaneous acute SDH in a middle-aged woman receiving dabigatran for cerebral venous thrombosis (CVT). Dabigatran reversal was achieved with idarucizumab and burr hole evacuation of the SDH was performed successfully. However, the patient suffered left posterior cerebral artery (PCA) territory ischemic stroke during this period, which appears to be a result of reversal of anticoagulant effect of dabigatran by idarucizumab. With this case report, we seek to highlight this rare complication of dabigatran therapy in CVT, the effectiveness of idarucizumab in reversing dabigatran action and the risks of interruption of dabigatran therapy with idarucizumab.